2015
DOI: 10.1021/jacs.5b11540
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Enigmazole A

Abstract: A highly convergent, stereocontrolled total synthesis of the architecturally complex marine sponge metabolite (−)-enigmazole A has been achieved. Highlights include an unprecedented late-stage large-fragment Petasis–Ferrier union/rearrangement, a multicomponent Type I Anion Relay Chemistry (ARC) tactic, and a dithiane–epoxide union in conjunction with an oxazole-directed stereoselective reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“… 10 The potential of each of the ARC tactics has been demonstrated separately in a number of completed or ongoing synthetic ventures, including those on (+)-spongistatin 1 and 2, 11 (+)-spirastrellolide A and B, 12 (−)-secu’amamine A, 13 and most recently (−)-enigmazole A. 14 Herein, we illustrate the strategic value of both types I and II ARC union tactics with a total synthesis of (−)-mandelalide A ( 1 ). In addition we demonstrate for the first time the combination of through-space negative charge migration, followed by a new CuCN-mediated cross-coupling of significant value for complex molecule synthesis.…”
mentioning
confidence: 99%
“… 10 The potential of each of the ARC tactics has been demonstrated separately in a number of completed or ongoing synthetic ventures, including those on (+)-spongistatin 1 and 2, 11 (+)-spirastrellolide A and B, 12 (−)-secu’amamine A, 13 and most recently (−)-enigmazole A. 14 Herein, we illustrate the strategic value of both types I and II ARC union tactics with a total synthesis of (−)-mandelalide A ( 1 ). In addition we demonstrate for the first time the combination of through-space negative charge migration, followed by a new CuCN-mediated cross-coupling of significant value for complex molecule synthesis.…”
mentioning
confidence: 99%
“…reported the first total synthesis of 1 and established the absolute configuration of the natural product in an unambiguous manner . Later, two additional total syntheses of 1 were disclosed by the Smith group and the Fürstner group …”
Section: Figurementioning
confidence: 97%
“…The synthesis of carboxylic acid 6 commenced with oxidation of known alcohol 11 , which is available in five steps from ( R )‐Roche ester, to the corresponding aldehyde, followed by dithioacetalization to provide dithiane 9 in 85 % yield for the two steps (Scheme ). Lithiation of 9 with t BuLi and coupling with epoxide 10 (HMPA, THF, −78 to −50 °C) afforded alcohol 12 in 76 % yield (88 % based on recovered 9 ).…”
Section: Figurementioning
confidence: 99%
“…Within them, 2,6‐disubstituted 4‐methylene tetrahydropyrans attract historically prolonged research interests as this moiety is observed as cores in a number of macrolactone natural products, such as enigmazole A and zampanolide, which exhibit potent and special anti‐cancer bioactivities (Scheme 1). [ 1 ] Several elegant synthetic strategies have been developed to construct this segment, including Smith's Petasis−Ferrier union/rearrangement strategy [ 2a ] and the intramolecular ene reaction. [ 2b ] Very recently, Trost et al .…”
Section: Background and Originality Contentmentioning
confidence: 99%